Book Review: Handbook of Global Supply Chain Management - Dr. Mamun Habib (International Journal of Supply Chain Management, 2013)
This handbook where each chapter was written by the people most qualified and the overall handbookis edited by a team was the best approach. In keeping with the global theme andthe goal of a handbook, the editors tried, in as many chapters as possible, tohave international scholars and practitioners involved. The editors hope theresult is a handbook that addresses, for each topic, the global extent theoryneeded by scholars who teach and research in this area and the specifies neededby practitioners. The editors hope this book brings clarity and comprehensiveinsight to the phenomenon of global supply chains and their management. Forstudents, this handbook aids in understanding the scope and specifies. Forpractitioners, this handbook provides additional insights into the nuances ofmanaging global supply chains. For researchers, this book generates additionalquestions, the answers to which will continue to enrich our understanding ofand ability to manage global supply chains.